Analysis of Women's Learning Needs Based on Local Wisdom in Darussalam Village - HHasibuan, Jubaidah; Mukarramah, Mukarramah; Handayani, Silvia Mariah; Dalimunthe, Khodijah Tussolihin; Irwan, Mahfuji (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Women in Darussalam Village play a crucial role in achieving food security by processing their harvests in simple ways. With their skills and creativity, they are able to create products with economic value and based on local wisdom. Through a strong spirit of mutual cooperation, local potential is collectively preserved, and the results are used for the common good. Based on field studies, women require innovation through knowledge and skills to cultivate local potential. Therefore, a learning needs analysis is necessary to identify the learning needs of productive-age women based on local wisdom. This study used a descriptive method with a qualitative approach. The results indicate that women in Darussalam Village have traditionally cultivated local potential and require learning related to hobbies and recreation, namely developing skills in making handicrafts for sustainable agricultural and fishery products, increasing productivity, and mentoring in product development for small businesses.